Worldwide variation in the performance of children and adolescents: An analysis of 109 studies of the 20-m shuttle run test in 37 countries - Olds, T.; Tomkinson, G.; Leger, L.; Cazorla, G. (Journal of Sports Sciences, 2006)
This study is a meta-analysis of 109 reports of the performance of children and adolescents on the 20-m shuttle run test (20-mSRT). The studies were performed in 37 countries and included data on 418,026 children, tested between 1981 and 2003. Results were expressed as running speed (km · h-1) at the final completed stage of the 20-mSRT. Raw data were combined with pseudodata using Monte Carlo simulation. The 20-mSRT performances were expressed as z-scores relative to all children of the same age and sex from all countries. An overall "performance index" was derived for each country as the average of the age- and sex-specific z-scores for all children from that country. Factorial analysis of variance was used to compare scores among countries and regions, and between boys and girls of the same age. There was wide and significant (P < 0.0001) global variability in the performance of children. The best performing children were from the Northern European countries Estonia, Iceland, Lithuania, and Finland (0.6 - 0.9 standard deviations above the global average). The worst performing children were from Singapore, Brazil, USA, Italy, Portugal, and Greece (0.4 - 0.9 standard deviations below the global average). There is evidence that performance was negatively related to being overweight, as well as to a country's average temperature.